PEMANFAATAN SUMBER PANAS PADA KOMPOR MENGGUNAKAN 10 TERMOELEKTRIK GENERATOR DIRANGKAI SECARA SERI UNTUK APLIKASI LAMPU PENERANGAN - Jojo Sumarjo; Aa Santosa; Muhammad Imron Permana (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2017)
Thermoelectric Generator is one of the alternative energy that uses differences temperature system uses to produce electrical energy. In the thermoelectric system, this generator uses stoves as the media to heat recovery that needed. Thermoelectric system that we researched was using 10 pieces of thermoelectric TEG-SP1848-27145 SA that arranged in a series with varieties of burning media such as firewood, gas LPG and spitrus. The use of different burning media affect the output of voltage that supplied by the thermoelectric. The difference temperature between the cold and hot side of termoelktrik generator (ΔT) when a steady state is 35 ° C using fuel wood, 39 ° C using a fuel gas and LPG and 20 oC using methylated. Optimal voltage is supplied by gas fuel LPG (ΔT) 39 ° C with output 1.62 volt.